2016
DOI: 10.2341/15-153-l
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Radiopacity of Bulk-fill Flowable Composites Using Digital Radiography

Abstract: New flowable composites that may be bulk-filled in layers up to 4 mm are indicated as a base beneath posterior composite restorations. Sufficient radiopacity is one of the several important requirements such materials should meet. The aim of this study was to evaluate the radiopacity of bulk-fill flowable composites and to provide a comparison with conventional flowable composites using digital imaging. Ten standard specimens (5 mm in diameter, 1 mm in thickness) were prepared from each of four different bulk-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
0
5
0
1
Order By: Relevance
“…According to the recommendations of the International Organization for Standardization (ISO 40490:2009) [ 16 ] restoration materials measuring 1 mm in thickness should have radiopacity equal to or greater than the same thickness of aluminum. According to results found in the literature [ 12 ] all tested materials followed the ISO 4049 standard and showed radiopacity value greater than a 1 mm step of the penetrometer scale, because it is known that the radiopacity material may vary according to the material thickness [ 17 ]. In the present study 10 mA, 65 kVp and 0.1 s were applied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the recommendations of the International Organization for Standardization (ISO 40490:2009) [ 16 ] restoration materials measuring 1 mm in thickness should have radiopacity equal to or greater than the same thickness of aluminum. According to results found in the literature [ 12 ] all tested materials followed the ISO 4049 standard and showed radiopacity value greater than a 1 mm step of the penetrometer scale, because it is known that the radiopacity material may vary according to the material thickness [ 17 ]. In the present study 10 mA, 65 kVp and 0.1 s were applied.…”
Section: Discussionmentioning
confidence: 99%
“…The composition of the composite resin has great influence on the radiopacity of the material [ 17 ]. To increase the radiopacity of dental restoration materials, elements with a high atomic number, such as barium, strontium, zirconia, and zinc, have been added to the inorganic phase of resins with no adverse effects on the other properties of these materials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study applying digital radiography proved that for all investigated bulk-fill flowable composites, significantly higher radiopacity values were evident in comparison with those of enamel, dentin and most of the conventional flowable composites (among them a self-curing material too). The majority of the manufactures’ values were close to the results of the studies; thus, it is concluded that the radiopacity data provided by the manufacturers can be trusted [ 59 ]. The incorporation of 3% n -TiO 2 in flowable composite slightly diminished the radiopacity values.…”
Section: Development Of Discussionmentioning
confidence: 66%
“…However, there are some problems associated with their poor mechanical properties, lower filler content, polymerization shrinkage and weak adhesion (1,3). Manufacturers have recently introduced new generation flowable composites, so called higher filler loading flowable resin composites, bulk-fill flowable composites and self-adhering flowable composites for elimination of negative effects and improving clinical requirements (3,5). Higher filler loading flowable resin composites for posterior restorations have better wear resistance compared with some resin composites (6).…”
Section: Introductionmentioning
confidence: 99%